Islamic Law and Customary Law Conflict in Elopement: A Sociological Study of the Bugis-Makassar Community - Ahmad Allimuddin; Rusdaya Basri; Rezki Amaliah Syafruddin; Naharuddin SR (Qanun: Jurnal Hukum Keluarga Islam, 2025)
Despite the existence of Marriage Law No. 1/1974 (amended by Law No. 16/2019) and the Compilation of Islamic Law that clearly regulate valid marriage requirements, the practice of elopement (silariang) in Bugis-Makassar communities remains prevalent, driven by the values of siri’ (honor) and the high burden of uang panai’, creating unresolved normative and material conflicts between Islamic law and customary law. This study aims to analyze these conflicts, their social impacts on family structures and gender inequality, and to propose a contextual legal harmonization model. Employing a qualitative sociological approach, data were collected through in-depth interviews with 15 key informants in Bone Regency and Makassar City, participatory observation, and document analysis, then analyzed using Miles & Huberman’s techniques (data reduction, data display, and conclusion drawing/verification). The most significant and distinctive finding is that silariang is not merely an economic escape but an active strategy to preserve family siri’ at the expense of the wali nikah requirement and children’s legal status. The consequences include fractured kinship ties, reinforced patriarchy, and legal vulnerabilities for children (lineage and inheritance). The study proposes harmonization through pre-marital mediation involving religious and adat leaders, transparent regulation of uang panai’, and integrated itsbat nikah services at KUA offices. This research contributes both theoretically and policy-wise by offering a harmonization model of legal pluralism that integrates maqāṣid al-sharī‘ah and siri’ values, replicable in other strong customary regions in Indonesia.